COMPARATIVE STUDY IN ENTREPRENEURSHIP INTENTION BETWEEN ECONOMICS AND BUSINNESS FACULTY OF MERCU BUANA UNIVERSITY AND ECONOMIC AND COMMUNICATION FACULTY OF BINA NUSANTARA UNIVERSITY - Siti Rohmawati , M. Havidz Aima , Hernawati W.R. Wiratih , Ikramina Larasati Hazrati Havidz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The condition of employment in Indonesia needs serious concern due to the high number of educated unemployed people. The high rate of unemployed people is also caused by the number of higher education alumni who prefer to be employees then entrepreneurs. One of the alternatives to suppress the number of unemployment and increase the employment is by having entrepreneurship through the entrepreneurship education. In this case, Mercu Buana University (UMB) and Bina Nusantara University (BINUS) are universities in Indonesia providing the entrepreneurship education. To know the difference of entrepreneurial intention models and the effects of internal and external factors on entrepreneurial intention mediated by entrepreneurial cognition, the present study was conducted. This quantitative study tests the measurement models and structural models using software SmartPLS 3.2.7 version and SPSS. Then, it is found that (1) inter-model, the model of entrepreneurial intention of UMB is not significantly different from BINUS; (2) intra-model, the internal and external factors positively, significantly influence the entrepreneurial cognition, but they do not significantly influence the entrepreneurial intention of both UMB and BINUS; (3) the entrepreneurial cognition significantly influences the entrepreneurial intention and significantly mediates the internal and external factors of entrepreneurial intention of both UMB and BINUS.